Efficiency of the proposed method of manufacturing temporary micropreparations of ticks of the genus Chorioptes - Kovalenko, S.; Melnychuk, V. (Scientific Progress & Innovations, 2022)
Acaroses of cattle are widespread and are recorded on all continents where they are grown. The causative agents of acaroses have a wide habitat, in particular, ticks of the genus Chorioptes occupy one of the leading places among other ectoparasites of the order Akariformes. Laboratory methods for the diagnosis of acaroses, including chorioptosis, are based on the detection of eggs, larvae, nymphs, and mature mites in skin scrapings, as well as their identification. To this end, it is recommended to produce micro preparations according to the proposed techniques. The research aimed to propose a method for the production of temporary micro preparations of ticks of the genus Chorioptes isolated from cattle. The proposed method belongs to the field of veterinary medicine, namely veterinary parasitology, and can be used for the preparation of anatomical and morphological preparations of ticks of the genus Chorioptes for their further identification to the species, as well as for the study of fauna and morphological and metric features in the structure of ticks of the genus Chorioptes. This method is characterized by the fact that live ticks of the genus Chorioptes are used to make total temporary preparations, where a two-component medium is used to fix them, which stains the parasites. The results of the studies show that the best staining of the morphological structures of the body of ticks of the species Chorioptes bovis (chelicerae, propodosomal and hysterosomal shields, ornament of the propodosomal shield, pelvis, ambulacra, bristles, palps) is provided by exposure of objects in the proposed mixture for 90 minutes. At the same time, under the condition of exposure for 10 minutes, the morphological features of seven structural elements of the tick's body had an unsatisfactory degree of coloration, one – satisfactory. Under the condition of exposure for 30 minutes, the morphological features of four structural elements of Chorioptes bovis ticks also had an unsatisfactory degree of coloration, four – satisfactory. Under the condition of exposure for 60 min. morphological features of four structural elements of Chorioptes bovis had a high level of coloration, three – satisfactory, one – unsatisfactory. The data obtained allow us to recommend the proposed method of manufacturing temporary micro preparations to improve the identification of permanent ectoparasites of the species Chorioptes bovis.